Association of Chocolate Spot and Faba Bean Rust Epidemics with Climate Change Resilient Cultural Practices in Bale Highlands, Ethiopia - Gosaye Eshetu; Yekedem Bimrew; Hassen Shifa (Advances in Agriculture)
Field survey was conducted in south eastern Ethiopia to determine the disease intensity of chocolate spot and rust and to investigate the association of disease intensity (incidence and severity) with environmental factors and crop cultural practices. A total of 280 faba bean fields were surveyed in eight districts, and type of cropping system, weed management practices, crop growth stage, previous crop in the field, and sowing date were recorded. The associations of disease intensity with independent variables were evaluated using logistic regression model. Mean disease incidence of chocolate spot varied from 70.9 to 93.2% in most fields while percentage severity index (PSI) ranged from 10.5 to 47.1%. In a reduced multiple variable model, chocolate PSI ≤ 30% showed high probability of association with mixed cropping system, good weed management practices, late planting, and when faba bean was rotated with vegetables and cereals. The mean disease incidence of faba bean rust was varied from 23.6 to 78.2%, while the mean PSI of rust was varied from 4.8 to 37.9%. In Gasera, Dinsho, and Agarfa districts, poor weed management practices, fields planted in the month of July, and when previous crop was legume had a high probability of association to (>20) rust PSI in a multiple variable reduced model. In contrast, soil types, fertilizer applied, and fungicides sprayed were not associated with disease intensity. The present study has identified cropping system, planting date, previous crop, district, and weed management practices as important variables that influence faba bean chocolate spot and rust epidemics in diversified fields. Therefore, proper weeding management practices, late planting, crop rotation habit, and other related farm practices should be carried out to reduce chocolate spot and rust impact until resistant faba bean genotypes are developed and distributed to the area.